THE FUNDAMENTALS OF AUTOMATIC PROCESSING OF ELECTRONIC TEXTS IN ACTIONS AGAINST REWRITING - Вавіленкова, А.І. (Science-based technologies, 2017)
The article is devoted to the problem of detecting so called surface rewrite. In this case the object of paraphrasing is checked in every sentence which structure is changed due to rewriting. The aim of the article is to formulate the basic criteria of rewriting of electronic text documents and a description of the formal conditions of their detection using logic and linguistic modeling. The study describes seven conditions under which, using comparison of logic and linguistic models can detect rewriting and which are derived based on the main modern methods of rewriting. Research of different methods of rewriting make it possible to identify patterns and the possibility of replacing the logic and linguistic models for the formal establishment of their identity